Effect of C/N Ratio and Physicochemical Conditions on the production of Rhamnolipids by Pseudomonas Aeruginosa LBI - Lovaglio, R. B. [UNESP]; Costa, S. G. V. A. O. [UNESP]; Lima, C. J. B. [UNESP]; Cortezi, M. [UNESP]; Contiero, Jonas [UNESP] (Research Journal Biotechnology, 2010)
Waste utilization for biosurfactant production is an important approach contributing to the reduction of waste treatment costs, while increasing the economic value of residues and reducing biosurfactant production costs: In an attempt to optimize rhamnolipid production by Pseudomonas aeruginosa LBI, the effects of the oil refinery waste as carbon source, C/N ratio, agitation speed, aeration rate, pH control and fed-batch culture conditions on the production of this biosurfactant were assessed in a bioreactor. Maximum production (16.9 g L(-1)) was attained at a C/N ratio of 23; agitation at 800 rpm and aeration at 2.0 vvm. The rhamnolipid solution (0.1%, w/v) exhibited surface and interface tensions of 25 mN/m and 0.63 mN/m respectively. The critical micelle concentration (CMC) was 73.9 mg L(-1). The optimal parameters used in this study promoted the formation of a useful biosurfactant with potential for many industrial applications.
Keywords: Rhamnolipids; C/N ratio; Soapstock; Aeration rate and Agitation speed